Carotid Intima-Media Thickness Is Associated With the Progression of Cognitive Impairment in Older Adults. Issue 4 (April 2015) - Moon, Jae Hoon; Lim, Soo; Han, Ji Won; Kim, Kyoung Min; Choi, Sung Hee; Park, Kyong Soo; Kim, Ki Woong; Jang, Hak Chul
Abstract : Background and Purpose—: We investigated the association between cardiovascular risk factors, including carotid intima-media thickness (CIMT), and future risk of mild cognitive impairment (MCI) and dementia in elderly subjects. Methods—: We conducted a population-based prospective study as a part of the Korean Longitudinal Study on Health and Aging. Our study included 348 participants who were nondemented at the baseline (mean age, 71.7±6.3 years) and underwent cognitive evaluation at the 5-year follow-up. Baseline cardiovascular risk factors were compared according to the development of MCI or dementia during the study period. Results—: At the baseline evaluation, 278 subjects were cognitively normal and 70 subjects had MCI. Diagnoses of cognitive function either remained unchanged or improved during the study period in 292 subjects (nonprogression group), whereas 56 subjects showed progression of cognitive impairment to MCI or dementia (progression group). The progression group exhibited a higher prevalence of hypertension and greater CIMT compared with the nonprogression group. Other baseline cardiovascular risk factors, including sex, body mass index, diabetes mellitus, insulin resistance, total cholesterol, waist-to-hip ratio, visceral fat, pulse wave velocity, and ankle-brachial index, were not significantly different between 2 groups. The association between greater baseline CIMT and the progression of cognitive impairment was maintained after adjustment for conventional baseline risk factors of cognitive impairment. Greater baseline CIMT was also independently associated with the development of MCI in the subjects whose baseline cognitive function was normal. Conclusions—: Greater baseline CIMT was independently associated with the risk of cognitive impairment, such as MCI and dementia in elderly subjects. Abstract : Supplemental Digital Content is available in the text.